Irony of a Global Village: A Spiritual Remedy for Alienation by Hindu Scriptures - Bhatta, Damaru Chandra (Literary Studies, 2023)
This article attempts to posit that modern people are alienated and so feel sad though they are equipped with modern means of comfort. This is ironical. In this connection, this article also attempts to define the concept of "a global village," discuss the psychological problems of alienation and loneliness, created ironically by globalization, and suggest some measures to cope with them from the perspective of the ancient wisdoms of the Hindu scriptural texts such as the Upanishad, the Bhagavad Gītā, the Pātanjali Yoga Sutras, and others. Unlimited, uncontrolled, and selfish desires are the main causes of modern alienation, triggered by the ideas of individualism, capitalism, consumerism, sexism, classicism, hedonism, and narcissism. Since the problems of alienation and loneliness are psychological ones, they can be best treated with the help of spiritual ideas propounded by ancient sages and seers. The permanent solution to these problems cannot be found outside in our external world. Their solutions can be found only inside our body, mind, and intellect with our inner journey to the Self ("Ātmā"). We can practice having vegetarian food, yoga, meditation, self-control over one's body and mind, mutual help, philanthropic activities, and non-violence by minimizing worldly desires, anger, and avarice to facilitate our journey to the Self. The less desires, the more happiness. This knowledge can inspire us avoid running after the temporary happiness attained by materialistic things. By being desireless and detached, we can remain still in the center of the inner Self inside our heart. This is the process of discovering permanent peace and happiness within ourselves to avoid the state of alienation.